Analisis Putusan PTUN Jakarta Nomor 540/G/2023/PTUN. JKT Tentang Pembatalan Keputusan Pensiun Dini Pegawai Negeri Sipil Perspektif Fiqh Siyasah - Ramadani; Ahmad Azril Akbar (Jurnal Hukum Lex Generalis, 2025)
This study aims to analyze the inhibition of honorable dismissal of civil servants who apply for early retirement by examining legal regulations and cases related to the inhibition of honorable dismissal of civil servants. The method used in this study is the normative legal method, while the approaches employed are the legislative approach, the conceptual approach, and the case approach. This study found that this obstruction of dismissal was carried out through the issuance of the Minister of Education, Culture, Research, and Technology's Decision No. 50804/M/11/2023, dated September 12, 2023, regarding the Revocation of the Decision on Honorable Dismissal at the Request of a Civil Servant in the Ministry of Education, Culture, Research, and Technology named Suroyo. The result of this study is the decision of the Jakarta Administrative Court No. 540/G/2023/PTUN.JKT, which states that the defendant, both procedurally and substantively, in issuing the subject of the dispute, has violated applicable regulations and has also violated the General Principles of Good Governance, particularly the principle of legal certainty, which has caused legal uncertainty regarding the plaintiff's status. Therefore, the plaintiff's lawsuit must be granted in full, and the disputed object is declared null and void. The defendant is required to revoke the Minister of Education, Culture, Research, and Technology's Decision No. 50804/M/11/2023, dated September 12, 2023, regarding the revocation of the decision to dismiss a civil servant in the Ministry of Education, Culture, Research, and Technology named Suroyo upon his own request.